2009
DOI: 10.1002/j.1556-6978.2009.tb00084.x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding School Counseling Internships From a Communities of Practice Framework

Abstract: School counseling interns are on the boundary of communities of practice. This study explored how school counselors develop competence during internship experiences by analyzing an online dialogue taking place among a small group of interns. Feelings of being on the boundary intensified with unsatisfactory supervisor‐intern relationships (lack of mutuality of engagement) or when interns experienced a sense of powerlessness to effect change at their internship placements (negotiating their repertoire). As bound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 33 publications
(37 reference statements)
1
22
0
Order By: Relevance
“…Although use of e-mail supervision has increased (Butler & Constantine, 2006;Woodside et al, 2009), its prevalence remains unknown. Moreover, investigations have yet to explore how the computer-mediated modality may impact general supervisory outcomes.…”
Section: Strengths and Limitationsmentioning
confidence: 98%
See 1 more Smart Citation
“…Although use of e-mail supervision has increased (Butler & Constantine, 2006;Woodside et al, 2009), its prevalence remains unknown. Moreover, investigations have yet to explore how the computer-mediated modality may impact general supervisory outcomes.…”
Section: Strengths and Limitationsmentioning
confidence: 98%
“…As such, counselor education programs are increasingly incorporating computermediated supervisory modalities into their training programs (Butler & Constantine, 2006;Woodside, Ziegler, & Paulus, 2009). In an investigation of e-mail correspondence as a supplement to clinical supervision, Clingerman and Bernard (2004) analyzed the frequency and content of 19 supervisees' weekly messages to their supervisor.…”
Section: E-mail Supervisionmentioning
confidence: 99%
“…He defined work engagement tasks that are necessary to transition into full membership within that community. Woodside, Ziegler, and Paulus (2009) applied the communities of practice research of Wenger (1998) to a study exploring 52 messages exchanged between five female school counseling interns over a 2-week period. The findings indicated that school counseling interns perceived numerous barriers in fulfilling work engagement tasks including: (a) a participant's "ability to interact with other members of the community"; (b) their development of "a shared repertoire of resources for negotiating meaning," including words, concepts, and ways of doing things; and (c) a sense of "accountability to the joint enterprise of the practice" (Woodside et al, 2009, pp.…”
Section: School Counselors' Professional Identitymentioning
confidence: 99%
“…Although scholars have called for the enhancement of the professional identity development of counselors (e.g., Gale & Austin, 2003), there remains uncertainty about how to operationalize and assess professional identity, as well as how to understand professional identity within specific systemic contexts (Ronnestad & Skovholt, 2003) or 'communities of practice' (Woodside, Ziegler, & Paulus, 2009). Defining community of practice and professional peer group membership is more complicated in the area of school counseling because school counselors are professional counselors, but also part of the educational team.…”
mentioning
confidence: 99%
“…Mutual engagement refers to members' interactions through which the individual spontaneously devotes himself or herself to particular community tasks to elicit other members' ongoing interactions (Guldberg and Mackness 2009). Joint enterprise is a concept to link different participants' ambitions, ideals and goals together, in order to achieve a shared vision or to implement a common value (Woodside et al 2009). Shared repertoire is formed by members' ongoing interactions (Cuddapah and Clayton 2011), through which people in a CoP will know each other well and enjoy being together.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%